(untitled) (Khairulummah, 2023)
The treaty of Elaf which was a commercial treaty among the Quraish and so many other tribes and countries comprising two super power Room (Italy) and Faris (Iran). The main purpose of this treaty was to offer protection for both sides conveys of commercial. The Quraish used to travel with northern tribes and countries in summer and southern tribes and countries in winter. This is their goodwill is the main reason that Allah mentioned him in his Holy Script. As well as the China-Pakistan Economic Corridor (CPEC) is a significant infrastructure economic development project that holds considerable importance for both China and Pakistan as well for all those countries which they have signed MOUs under the umbrella of BRI. CPEC aims to boost and enhance strategic geopolitical significance, Economic development, connectivity, Energy security and Trade expansion between both countries. The project has sparked geopolitical tensions in the region as well, particularly with India, which has expressed reservations about the project’s route. We as Muslims should ensure that this project does not fall prey to conspiracy theories. This research will try to find out how the ELAF and CPEC are historically related. Because the objectives of both are identical. That’s why we will analyzed both treaties in the context of Sura e Quraish.